Cidade memória e patrimônio : a expriência de tombamento do Edifício Sede da CMNP - Companhia Melhoramentos Norte do Paraná (Set. 2003 - Nov. 2004) - Tomaz, Paulo Cesar (2008)
The present lecture has as an achievement to reflect about the preservation of culture estate having this case studying about a falling over building headquarters from the Companhia Melhoramentos Norte do Paraná (CMNP), in Maringa, this building was very important for the commercial activities in this company that was utilized strategically in the process of reoccupation from all the known area like Parana North Region. Also they analise the preservation of the cultural property in the state of Parana, looking forward to elucidate the mainly events that were moulded its policy of the preservation in the results for the elaboration of strategies that would reduce the contradictions and cultural differences existed in there.The study follows the formation of Maringa's city, analising the development from the influence of the Companhia Melhoramentos Norte do Paraná, seeing that the comprehension of the history and memory of the city is closely related with the trajectory of the company and its space. In this context, the falling over building meant an act of preservation in the historical memory of the city and of its cultural estate that in the same time triggered off measures geared towards to consolidate a policy of the preservation of the cultural estate for all the community. In the execution of this work was utilized a vast range of documentary sources like pictures, interviews, journalistic articles, judicial resolutions, community laws and so far. Those came to enrich the historical research in its more varieded aspects.